Deep Learning application to model learning in cognitive robotics - Rodríguez-Jiménez, Ariel (2020)
The kind of training used for an artificial neural network will depend on factors such as: available data, training time, hardware resources, etc. The trainings can be online and offline. In the current article we experimented with online trainings on a robot whose main characteristic is the usage of a Cognitive Darwinist Mechanism to survive. The robot learns in real-time. It has deep artificial neural networks to predict actions, it’s trained using the least amount of storage and the training time has to be as fast as possible; keeping high confidence in the artificial neural network. The experimental trainings are: Online Deep Learning, Online Deep Learning with memory and Online Mini-Batch Deep Learning with memory.